Improving banking supervision - David G. Mayes (Bank of Finland, 1998)
This paper explains how banking supervision within the EU, and in Finland in particular, can be improved by the implementation of greater market discipline and related changes.Although existing EU law, institutions, market structures and practices of corporate governance restrict the scope for change, substantial improvements can be introduced now while there is a window of opportunity for change.The economy is growing strongly and the consequences of the banking crises of the early 1990s have been worked through.Greater market discipline, in the form of a regime of quarterly public disclosure by banks of their capital adequacy, peak exposures and risk management systems, along with improved incentives, will help improve the prudential management of banks, reduce the costs of supervision, enable supervisors to focus on systemic risks and help customers determine the risks they face.Banking inherently involves the taking of risks, but transparency and improved public information about them will help all concerned manage the risks more effectively and greatly reduce the chance that the taxpayer will again be called upon to help rescue the banking system.
URN:NBN:fi:bof-20140807363
Keywords: 330; Banking supervision; market discipline; disclosure; systemic risk; financial system oversight